Designing for Children: What Do Human Factors Professionals Need to Know?. (September 2015) - Berg Rice, Valerie J.; Brickman, Dennis; Lueder, Rani; Smith-Jackson, Tonya; Vredenburgh, Alison; Zackowitz, Ilene
Human Factors and Ergonomics (HF/E) research, projects, expert witness cases, and product designs that target children and their caretakers require a unique set of knowledge and skills. Panelists will describe some of their professional child-focused practices and explain how their education and experiential backgrounds prepared them for this work. In cases where traditional HF/E training was not sufficient, panelists will describe how they met this challenge. The discussion between panelists and attendees will focus on suggestions for preparing HF/E professionals for working with this target market.